PRODUCTION OF VINEGAR FROM AN ALCOHOLIC 1 BEVERAGE OF 2 ANDEAN BERRY (Vaccinium meridionale SW), MEASUREMENT OF 3 ANTIOXIDANT ACTIVITY AND EVALUATION OF CYTOTOXIC EFFECT ON 4 COLON CANCER CELLS SW480 - Zapata Vahos, Isabel Cristina; Ochoa Agudelo, Susana; Alzate Arbelaez, Andres Felipe; Zapata Zapata, Arley David; Rojano, Benjamin Alberto (Vitae, 2020)
BACKGROUND: Vaccinium meridionale presents fruits with a high content of phenolic compounds and anthocyanins and therefore a high antioxidant capacity. OBJECTIVE: The aim was the production of vinegar from three treatments of berries alcohol beverage, to evaluate its antioxidant and cytotoxic activity. METHODS: Vinegars were prepared by acetic fermentation from alcoholic beverages of Andean berries by three treatments: mechanical maceration, heating, and mixing. The titratable acidity and acetic acid content were evaluated in the vinegar; antioxidant potential (DPPH, FRAP, and ORAC); content of antioxidant metabolites (total polyphenols, total anthocyanins, and phenolic hydroxycinnamic acids) were evaluated in the juice, alcoholic beverages, and vinegar; the antiproliferative capacity in colon cancer cell SW480 was determined in vinegar. RESULTS: Alcoholic beverages presented the main antioxidant activity. However, after the acetic fermentation, it was observed a fall in the antioxidant potential in all techniques evaluated in three treatments. The vinegar obtained by heated and mixed treatments were presented the highest values in antioxidant activity, phenols, and anthocyanins. Antiproliferative activity inhibitions of vinegars in cell viability were 6.2% (20 μg/mL) and 22.5% (200 μg/mL). CONCLUSIONS: Production of acetic acid is independent of the treatment. The antioxidant activity is favored in alcoholic beverages with the treatment of hot maceration. Andean berry CAL vinegar has antiproliferative activity, inhibiting a colon carcinoma SW480 line although in a low amount compared with reports in the literature.